Plan de internacionalización de la cadena Tostao' Cafe & Pan (2019)
Through a data analysis in order to study the company TOSTAO’ Café & Pan, it’s clear its potential to make an expantion move to other markets. This happen because its essence and system that make it triumph in Colombia, it’s highly applicable within other countries. However, It must have the certency about how, where, who, and why. These kind of products that Tostao’ sells, the way and the price of them, have become these company in a giant of the colombian coffee industry without no doubt. The acceptance and affection of the people it’s obvious, and even thought it’s not easy to have this achievement in another foreign country, it could happen with an established plan. The coffee culture paradigm in other countries it’s the first barrier that this company might run into along the way because the coffee, for much people, it’s not about price, conversely, it’s about quality and experience. Therefore, these possible situations have to be previously analyzed and immersed in this internationalization study.